Case of Hereditary Papillary Renal Cell Carcinoma Type I in a Patient With a Germline MET Mutation in Russia - Mikhaylenko, Dmitry S.; Klimov, Alexey V.; Matveev, Vsevolod B.; Samoylova, Svetlana I.; Strelnikov, Vladimir V.; Zaletaev, Dmitry V.; Lubchenko, Ludmila N.; Alekseev, Boris Y.; Nemtsova, Marina V. (Frontiers in Oncology, 2020)
Hereditary papillary renal carcinoma (HPRC) is a rare autosomal dominant disease characterized by the development of multiple papillary type I renal cell carcinomas. This hereditary kidney cancer form is caused by activating mutations in MET. Descriptions of patients with HPRC are scarce in the world literature, and no cases have been described in open sources in Russia. Here, we describe a 28-year-old female Russian patient with 7 and 10 primary papillary renal cell carcinomas in the left and right kidneys, respectively. The patient did not have a family history of any of the known hereditary cancer syndromes. A comprehensive medical examination was performed in 2016 including computed tomography and pathomorphological analysis. The observed tumors were resected in a two-step surgical treatment. In February 2019, no sign of disease progression was detected in follow-up medical examination. Molecular genetic analysis revealed the germline heterozygous missense variant in MET: c.3328G>A (p.V1110I; CM990852). We have discussed the biological effects of the detected mutation and the utility of DNA diagnostics for treating patients with HPRC.